تغير الخواص الميكانيكية للبيتون المصنع باستخدام الحصويات البيتونية المعاد تدويرها - عماد فاضل (Tishreen University, 2017)
أدتالزيادة الكبيرة في حجم نفايات الهدم البيتونية وتأثيرها على البيئة إلى إعادة النظر في استخدام ركام الهدم البيتوني كبديل جزئي أو كلي عن الحصويات الطبيعية، والعمل على إنتاج بيتون جديد يحقق الخواص المطلوبة لاستخدامه في المنشآت الهندسية[1]. مع التنويه إلى إمكانية تحسين بعض الخصائص الميكانيكية لهذا البيتون من خلال معالجة هذه الحصويات قبل استخدامها، أو تدعيم هذا البيتون بالألياف لتحسين سلوكه الإنشائي. يعالج هذا البحث دراسة استبدال الحصويات الطبيعية المستخدمة في البيتون بحصويات بيتونية معاد تدويرها ناتجة عن ركام الهدم وذلك وفق نسب استبدال مختلفة تتراوح بين 0%، 25%، 50%، 75%، 100%، وتأثير ذلك على سلوك البيتون مقارنة مع البيتون ذي الحصويات الطبيعية، مع تحديد نسبة الاستبدال المثلى. أظهرت النتائج انخفاض نسبي في مقاومة البيتون على الضغط البسيط، وانخفاض محدود للكتلة الحجمية أيضاً، و تعديل طفيف على سلوك البيتون تحت تأثير التحميل وذلك بزيادة نسبة استبدال الحصويات الطبيعية بحصويات بيتونية معاد تدويرها. The large increase in the volume of demolition concrete waste and its impact on the environment has led to reconsider of using concrete demolition rubble as a partial or a whole alternative of natural aggregates to produce new concrete which has the required properties to use in engineering constructions[1]. With the possibility of improving the mechanical properties of this concrete by processing this aggregates before using it or support this concrete with fiber to improve its structural behavior. This research deals with the study of the replacement the natural aggregates used in concrete with recycled concrete aggregates resulting from the demolition rubble , according to different replacement ratiosranging between 0 % -25 % -50 % -75 % -100% and the impact on the concrete behavior with a natural aggregates and determine the optimal replacementpercentage. The results showed a relative decrease in the concrete resistance on the simple pressure , limited decrease in the volumetric mass also, and a slight adjustment to the behavior of concrete under the loading effect by increasing the replacement proportion of the natural aggregateswith recycled concrete aggregates..